Adolescent Sexual Moral Education: An Integrative Analysis of Prophetic Hadith, Kohlberg’s Moral Development Theory, and Field-Based Evidence - Agus Susilo Saefullah; Ila Nurlaila Hidayat; Muhammad Azdzahaby Al Faraya; Naufal Syauqi Fauzani; Muhammad Imam Asy-Syakir (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2026)
Adolescent sexual moral education has become increasingly urgent amid the normalization of permissive relationships and the pervasive influence of digital media. This study aims to develop an integrative understanding of adolescent sexual moral education by analyzing Prophetic Hadith in relation to Kohlberg’s moral development theory and field-based evidence. Employing a qualitative approach with a primary emphasis on field research, data were collected through in-depth interviews with four informants (I1–I4) actively involved in adolescent education. These empirical findings are interpreted through an analytical framework grounded in Prophetic Hadith and Kohlberg’s stages of moral development. The findings reveal that the Prophet’s dialogical-empathetic approach functions as a transformative pedagogical process that guides adolescents’ moral reasoning from pre-conventional orientations toward more socially and internally grounded moral awareness. While this process aligns with Kohlberg’s developmental stages, it also extends them by incorporating a transcendental dimension rooted in spiritual accountability. Field-based evidence indicates that adolescents tend to normalize permissive interactions influenced by social and digital environments, highlighting the need for moral education grounded in dialogue, empathy, and internal awareness. This study demonstrates that the integration of prophetic pedagogy, moral development theory, and empirical realities constitutes a genuine epistemological dialogue, contributing to a context-sensitive and integrative model of adolescent sexual moral education